Analisis pemungutan pajak restoran menurut Perda Kota Manado No. 2 Tahun 2011 pada Badan Pendapatan Daerah Kota Manado - Manengkey, Tesalonika Ave; Warongan, Jessy D. L.; Mintalangi, Syermi S. E. (Riset Akuntansi dan Portofolio Investasi, 2025)
One of the regional taxes with growing potential, as service sector components are increasingly emphasized in development policies to support economic growth, is the restaurant tax. According to Manado City Regional Regulation No. 2 of 2011, Part II concerning Regional Taxes, the Restaurant Tax is a tax on services provided by restaurants. A restaurant is a facility that provides food and/or drinks for a fee, including restaurants, cafeterias, canteens, stalls, bars, and similar establishments, including catering services. This research aims to analyze the collection process of restaurant tax according to Manado City Regional Regulation No. 2 of 2011 at the Manado City Regional Revenue Agency. The analytical method used is descriptive. The research results show that the procedure for collecting restaurant tax is carried out by taxpayers visiting the tax office. The procedure for paying restaurant tax is through self-assessment. Taxpayers can make payments online via mobile banking, banks, or other payment channels provided by Bapenda. The restaurant tax collection procedure is conducted through field visits with an assignment letter from the office to remind and collect payments from taxpayers who have not paid their bills. Restaurant tax bookkeeping is done when taxpayers pay via a smart card system. Incoming payments are immediately recorded, summarized, and reconciled with the amount deposited into the account.